2010
DOI: 10.1097/brs.0b013e3181bf8efe
|View full text |Cite
|
Sign up to set email alerts
|

Contributory Factors to Postoperative Spinal Fusion Complications for Children With Myelomeningocele

Abstract: Positive urine cultures obtained before spinal surgery for children with MMC significantly increased the risk for perioperative wound (P=0.002). Urinary tract infections can be easily detected and treated. We believe urinary culture, protein deficiencies, or Hct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 27 publications
3
41
0
3
Order By: Relevance
“…25,28 As both presented individual patient characteristics with related outcome data, these participants were excluded from univariate statistical analysis. Three papers excluded neonates: Rojratsirikul et al excluded infants aged less than two months, 27 whilst Secker and Jeejeebhoy and Stey et al excluded neonates aged <31 days and <28 days, respectively.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…25,28 As both presented individual patient characteristics with related outcome data, these participants were excluded from univariate statistical analysis. Three papers excluded neonates: Rojratsirikul et al excluded infants aged less than two months, 27 whilst Secker and Jeejeebhoy and Stey et al excluded neonates aged <31 days and <28 days, respectively.…”
Section: Search Resultsmentioning
confidence: 99%
“…23 Four studies were undertaken in cardiac surgical populations, 13,20,21,29 and four studies were undertaken in general surgical populations, mainly gastrointestinal/abdominal surgery. 16,17,26,27 Two studies were performed in spinal surgical populations, 25,29 and one study comprised of cardiac, neurosurgical and general surgical participants. 24 Stey et al reported on all children undergoing any type of surgery with data entered on to the American College of Surgeons National Surgical Quality Improvement Program Pediatric Report Form.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations